2021
DOI: 10.7554/elife.64984
|View full text |Cite
|
Sign up to set email alerts
|

Shape deformation analysis reveals the temporal dynamics of cell-type-specific homeostatic and pathogenic responses to mutant huntingtin

Abstract: Loss of cellular homeostasis has been implicated in the etiology of several neurodegenerative diseases (NDs). However, the molecular mechanisms that underlie this loss remain poorly understood on a systems level in each case. Here, using a novel computational approach to integrate dimensional RNA-seq and in vivo neuron survival data, we map the temporal dynamics of homeostatic and pathogenic responses in four striatal cell types of Huntington’s disease (HD) model mice. This map shows that most pathogenic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Langfelder et al 27 observed significantly increased TCERG1 expression in the striata of Q111, Q140, and Q175 mice relative to wild type. However, this has been suggested to be a compensatory homoeostatic response to promote neuron survival 28 , and such an effect would be difficult to model in a human eQTL sample. Therefore, it is possible that increased TCERG1 expression is associated with earlier onset of HD but corroborating evidence from other samples or direct experimentation is required for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Langfelder et al 27 observed significantly increased TCERG1 expression in the striata of Q111, Q140, and Q175 mice relative to wild type. However, this has been suggested to be a compensatory homoeostatic response to promote neuron survival 28 , and such an effect would be difficult to model in a human eQTL sample. Therefore, it is possible that increased TCERG1 expression is associated with earlier onset of HD but corroborating evidence from other samples or direct experimentation is required for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Langfelder et al [27] observed significantly increased TCERG1 expression in the striata of Q111, Q140 and Q175 mice relative to wild type. However, this has been suggested to be a compensatory homeostatic response to promote neuron survival [28], and such an effect would be difficult to model in a human eQTL sample. Therefore, it is possible that reduced TCERG1 expression is associated with later onset of HD but corroborating evidence from other samples or direct experimentation is required for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…102 Computational analyses of RNA-seq data and neuronal survival indicated that neuronal loss was largely driven by the loss of homeostatic support in both neurons and astrocytes. 103 Landmark evaluations of the brain vasculature also show activation of innate immune signals and reduction of proteins involved in BBB maintenance (within astrocytes). 104 Together, the availability of large data sets reporting how astrocytes change at a molecular level and in a cell-specific manner in both mice and humans as HD severity increases holds the promise that key mechanisms can be carefully identified and functionally evaluated in vivo in order to prove or refute their causal roles.…”
Section: Astrocytic Gene Expression Changes In Hdmentioning
confidence: 99%